Electromechanical Modeling of Rolling Spherical Triboelectric Nanogenerators Considering Nonlinear Effects. Issue 12 (15th September 2022) - Han, Qinkai; Jiang, Ziyuan; Shao, Qingyang; Gao, Shuai; Chu, Fulei
Abstract: In this study, electromechanical coupling modeling and analysis of the rolling spherical triboelectric nanogenerators (RS‐TENG) considering nonlinear effects are conducted. After a brief review of the power generation mechanism, a capacitance‐fitting model of the RS‐TENG spherical electrode is proposed. By using the energy principle and differential equations of equivalent circuits, an electromechanical coupling model is established by considering the nonlinear variation in the dielectric sphere rolling angle. Using the harmonic balance method (HBM), the dynamic output characteristics of the RS‐TENG are analytically solved. Numerical integration and dynamic tests are used to verify the accuracy of HBM results. By comparing the changes in the RS‐TENG output performance with and without the nonlinear effect, it is shown that the model proposed in this study can effectively avoid the underestimation of the operation bandwidth (a relative increment of 43%) and overestimation of the maximum power density (a relative decrement of 32%), and significantly improve the accuracy of the RS‐TENG performance estimation. The influence of design parameters on the dynamic output characteristics of the system is discussed. The fitting coefficients obtained from the parameter influence discussion can be used as the basis for the RS‐TENG output performance design. Abstract : Electromechanical coupling analysis of rolling spherical triboelectric nanogenerators considering nonlinear effects is conducted. Dynamic output characteristics are analytically solved. The model proposed in this study can effectively avoid the underestimation of the operation bandwidth (a relative increment of 43%) and overestimation of the maximum power density (a relative decrement of 32%), and significantly improve the accuracy of performance estimation.